Factors Affecting Young Consumers’ Intention to Purchase Upcycled Fashion Products – A Case Study in Vietnam - Van Tuan Pham; Vu Thanh Xuan; Nguyen Minh Trang; Phung Mai Thanh Hang; Nguyen Thao Nguyen (Journal La Bisecoman, 2021)
In this study, the author has given different basis to build hypothesis and research models to find out the factors affecting the Vietnamese young consumer's intention to purchase upcycled fashion products. Firstly, this paper focuses on studying the relationship between attitudes and purchase intentions. Secondly, the author studies the effects of factors on attitudes and purchase intentions. The main research subjects are factors affecting Vietnamese young consumer' intention to to purchase upcycled fashion products. Hence, this research was conducted based on survey results among 400 young people aged 18 to 34 in Hanoi and Ho Chi Minh city which are two big city in Vietnam. The authors used two statistical software, SPSS 26.0 and AMOS 20.0, to analyze the survey results. These tools help the authors analyze Cronbach's Alpha reliability coefficients, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), structural equation model (SEM). The results show that there was a positive relationship between young consumers' attitudes and purchase intention in the Vietnamese context. Attitude mediates the relationship between the influencing factors and purchase intention. Moreover, the study test the impact of five main factors including environmental concern, social value, uniqueness value, perception financial risk, and perceive quality risk. The environmental concern (β = 0.337) is considered as the strongest effect on consumers' attitudes towards products. The factors such as uniqueness value (β = 0.302) as well as social value (β = 0.216) also positively affect consumers' attitudes. On the other hand, perception financial risk (β = -0.168), and perceive quality risk (β = -0.280) negatively affect consumers' attitudes